Respuesta :
You can see here that x = 0. Follow the step-by-step attached and read here.
1) Subtract 2x from both sides, which cancels the two terms shown with a strikethrough.
2) Subtract 6 from both sides, which cancels the +6 from the right-hand side.
3) Distribute the negative sign to (3+2x).
4) Add 3 to both sides, which cancels the two terms shown with a strikethrough.
5) Divide both sides by -2. (Zero divided by any number is zero)
6) x = 0
1) Subtract 2x from both sides, which cancels the two terms shown with a strikethrough.
2) Subtract 6 from both sides, which cancels the +6 from the right-hand side.
3) Distribute the negative sign to (3+2x).
4) Add 3 to both sides, which cancels the two terms shown with a strikethrough.
5) Divide both sides by -2. (Zero divided by any number is zero)
6) x = 0
![Ver imagen susanwiederspan](https://us-static.z-dn.net/files/d39/cfb39dfb5173592d606e8aeb6083c9c0.png)
2x+3=2x-(3+2x)+6
begin with the parentheses
the minus sign changes all signs
inside the parentheses
2x+3=2x-3-2x+6
combine like terms
2x-2x= 0 so it cancels itself
2x+3=3
subtract 3 from both sides
2x=0
divide both sides by 2
x=0
Check:
substitute x=0 in equation
2x+3=2x-(3+2x)+6
2(0)+3=2(0)-(3+2(0))+6
0+3=0-(3+0)+6
3=-3+6
3=3
Hope this helps!! :)
begin with the parentheses
the minus sign changes all signs
inside the parentheses
2x+3=2x-3-2x+6
combine like terms
2x-2x= 0 so it cancels itself
2x+3=3
subtract 3 from both sides
2x=0
divide both sides by 2
x=0
Check:
substitute x=0 in equation
2x+3=2x-(3+2x)+6
2(0)+3=2(0)-(3+2(0))+6
0+3=0-(3+0)+6
3=-3+6
3=3
Hope this helps!! :)